Effects of Hydraulic Retention Time on Process Stability of Integrated Fixed Film Activated Sludge (IFAS) Biological Wastewater Treatment Process - Neamsungneon, Nussara; Sriwiriyarat, Tongchai (Burapha Science Journal, 2026)
The objective of this study was to evaluate the effects of hydraulic retention time (HRT) on the stability of Integrated Fixed Film Activated Sludge (IFAS) wastewater treatment process. The experiments were conducted by two pilot-scale Modified Ludzack-Ettinger (MLE) systems, i.e., the system installed with Bioweb media in the aerobic zone at the filling volume of 34.5% v/v, so-called as IFAS system, and the system operated without media installed, so-called AS system. Both systems were operated at different HRTs of 8, 6 and 4 hours, at the solid retention time (SRT) of 8 days, and at the temperature of 28 ± 2 oC. The results revealed that the organic removal efficiencies were 90.4 ± 0.6%, 88.7 ± 3.2%, and 84.2 ± 10.2%, respectively, in AS system and were 87.6 ± 3.0%, 85.4 ± 3.7% and 87.7 ± 4.8%, respectively, in IFAS system. Nitrification were 99.2 ± 0.5%, 99.4 ± 1.1%, and 97.9 ± 0.5%, respectively, for AS system and were 85.1 ± 5.61%, 84.3 ± 6.6%, 67.5 ± 5.6%, respectively, for IFAS system, at the HRTs of 8, 6, and 4 hours, respectively. The reductions of HRTs had the negative effects on the organic removal efficiencies in the AS system because sludges were washed out from the final clarifier due to insufficient settling time and excessive filamentous bacteria resulting in bulking sludge. The negative effects of HRT were resulted in the IFAS system for nitrification because the diffusion time of substrates into the biofilm layers were limited at higher flowrates. It appears that the capacities of AS system for organics and nitrogen removals were higher than IFAS system at the SRT of 8 days and at the HRTs of 8, 6 and 4 hours, respectively, due to the limitations of substrates diffusion. The results indicate that the HRT has a negatively impact on the stability of IFAS system at the SRT of 8 days and the conventional AS should be used instead for the wastewater treatment.